Analysis of the Use of the DILA BISA Multimedia-Based Application on Arabic Language Learning at the Mubtadi' Level at Elementary School - Nabiilah, Alaikin; Furoidah, Asni; Zainuri, Zainuri; Syafril R, Raihan Ammar (UAS PRESS, 2026)
Arabic language learning at the mubtadi' level in Elementary Schools is currently still hampered by various factors, such as less interesting learning methods, limited learning media, and lack of student learning motivation. Therefore, innovation is needed in Arabic language learning to improve student interest and learning outcomes. One innovation that can be implemented is the use of the DILA BISA multimedia-based application. This study aims to analyze the use of the DILA BISA multimedia-based application in Arabic language learning at the mubtadi' level at elementary school. This study uses a qualitative method with a case study research approach. Research data were collected through observation, interviews, and documents. The results show that the use of the DILA BISA multimedia-based application can improve student interest and learning outcomes in Arabic language learning at the mubtadi' level at elementary school. This is evidenced by increased student participation in learning, increased student understanding of Arabic language materials, and increased student test scores.